PENGARUH FREE CASH FLOW, STRUKTUR AKTIVA, KEBIJAKAN DIVIDEN DAN OPERATING LEVERAGE TERHADAP KEBIJAKAN UTANG PADA PERUSAHAAN PERTAMBANGAN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Panjaitan, Rahel Rika Susanti; Augusta, Ivana; Putri, Celine Cendana; Wijaya, Selly; Sitorus, Friska Darnawaty; Dwi Syah Putri, Tantri Octora (EDUTECH CONSULTANT, 2019)
The objective of the study is to test and analyze the effect of free cash flow, asset structure, dividend policy and operating leverage to the debt policy of companies at coal mining listed in the Indonesia Stock Exchange (IDX) in the period of 2012-2016. The research used some theories of free cash flow, asset structure, dividend policy and operating leverage. The research was used by a quantitative research approach, this research was causal/clausal. The data collection of this research was performed by study documentation. This research uses secondary data types and sources. The research concluded that free cash flow, asset structure, dividend policy and operating leverage simultaneously have a positive and significant effect on the debt policy of companies at coal mining listed in the Indonesia Stock Exchange in the period of 2012-2016. In partial, asset structure have positive and significant effect on the debt policy, while free cash flow, dividend policy and operating leverage have no effect on the debt policy.